IMPROVING THE USER SURVEY OF UNIVERSITAS MURIA KUDUS BASED ON INFORMATION TECHNOLOGY TO MAXIMIZE THE RESULT IN SUPPORTING ACCREDITATION OF HIGHER EDUCATION INSTITUTION (AIPT) 3.0 - Muhammad Arifin; Farid Noor Romadlon (Universitas Muria Kudus, 2020)
Alumni or graduates are the key of university's accountability. Alumni who are well accepted in the working place, whether they are entrepreneurial or working with other people, are able to become the basis of the institution existence to get a trust. User survey is a must for university because it is a compulsive point that must be completed in preparing accreditation forms for both universities and departments. The use of information technology media is expected to increase its maximum results at score 4. This study aims to determine the use of information technology in implementing user survey at Universitas Muria Kudus. The results obtained are quite good. The use of information technology in the user survey has been carried out in almost every stage of the activity. These stages were collecting data from the alumni website and then identifying the departments. The next was blasting information on tracer study activities and procedures to alumni via email and WhatsApp group of alumni in each department. After the alumni had filled out the questionnaire through career center (PKPA) website, respondents’ data were classified based on the name of the workplace, alumni, and departments. After that, alumni assessment questionnaire was sent via post to alumni users, which was attached with the names of the alumni. It was then confirmed via WhatsApp and or email to HRD or Contact Person at the alumni workplace two weeks after sending. The number of workplace (companies/agencies/schools) which responded was quite good. There were 83 workplaces responded back the assessment by post or email. The result of user survey is inecessary as an input for institutions in escalating the quality of graduates.